Miracle of Wan-Whale: Children Puppet Theatre for Presenting about Littering Issues - Pukha, Kedsiree; Rueangsanchai, Natthachai; Pradabpachr, Patsiri; Akkapram, Pachaya (Journal of Fine and Applied Arts Khon Kaen University, 2021)
This article discusses the operation and findings from the process of creating a puppet theater for children entitled Wonders of the Whale’s Day. The research was primarily aimed at finding the effective path to create a puppet theater that can deliver a message and build awareness of the issues of littering to the children audience aged 9-12 years old. The process of creation was divided into 3 parts; 1) Writing a script, 2) Making the puppets, and 3) Directing and creating a puppet theater play. The result showed that Wonders of the Whale’s Day was able to deliver the desired message and build awareness of the issues of littering to the targeted audience. Furthermore, some types of waste, such as paper, plastic, foam, can also be recycled as a raw material for creating puppets and the visual elements on stage beautifully.